The Effect of Vertical and Oblique Inclinations on Fracture Stability and Reoperation Risks in Femoral-Neck Fractures of Nongeriatric Patient - Jiang, Dajun; Zhan, Shi; Hu, Hai; Zhu, Hongyi; Zhang, Changqing; Jia, Weitao (Frontiers in Bioengineering and Biotechnology, 2021)
Background: For nongeriatric patients with femoral neck fractures (FNFs), preoperative evaluation of fracture three-dimensional inclination is essential to identify fracture stability, select appropriate fixation strategies, and improved clinical prognoses. However, there is lack of evaluation system which takes into account both vertical and oblique inclinations. The purpose of this study was to comprehensively investigate the effect of vertical and oblique inclinations on fracture stability and reoperation risks. Methods: We retrospectively reviewed the medical records of 755 FNFs patients with over two years follow-up. The 3-D inclination angle in vertical (α) and oblique plane (β) were measured based on CT images. The optimal threshold for unstable 3-D inclination were identified by seeking the highest Youden Index in predicting reoperation and validated in the biomechanical test. According to the cut-off value proposed in the diagnostic analysis, forty-two bone models were divided into seven groups, and were all fixed with traditional three parallel screws. Interfragmentary motion (IFM) was used for comparison among seven groups. The association between reoperation outcome and 3-D inclination was analysed with a multivariate model. Results and Conclusion: The overall reoperation rate was 13.2%. Unstable 3-D inclination angles with an optimally determined Youden index (0.39) included vertical (α>70°) and oblique (50°<α<70° and β>20° / β<-20°) types. Biomechanical validation showed these fractures had significantly greater (p<0.05) interfragmentary motion (1.374-2.387 mm vs. 0.330-0.681 mm). The reoperation rate in 3-D unstable group (32.7%) is significantly (p<0.001) higher than that in 3-D stable group (7.9%). Multivariate analysis demonstrated that 3-D inclination angle was significantly (OR=4.699, p<0.001) associated with reoperation. FNFs with α>70°; 50°<α<70° and β>20°/ β<-20° are real unstable types with significantly worse interfragmentary stability and higher reoperation risks. Fracture inclination in vertical and oblique planes is closely related to reoperation outcomes and may be a useful complement to the way FNFs are currently evaluated.